Business as Usual: A Lack of Institutional Innovation in Global Health Governance: Comment on "Global Health Governance Challenges 2016 – Are We Ready?" - Lee, Kelley (Int J Health Policy Manag, 2016)
There were once again high expectations that a major global health event - the Ebola virus outbreak of 2014-2015 - would trigger meaningfully World Health Organization (WHO) reform and strengthen global health governance (GHG). Rather than a "turning point," however, the global community has gone back to business as usual. This has occurred against a backdrop of worldwide political turmoil, characterised by a growing rejection of existing political leaders and state-centric institutions. Debates about GHG so far have given insufficient attention to the need for institutional innovation. This entails rethinking the traditional bureaucratic model of postwar intergovernmental organizations which is disconnected from the transboundary, fast-paced nature of today’s globalizing world.